Peirce as an Experimental Psychologist. - Cadwallader, Thomas C. (Transactions of the Charles S. Peirce Society)
Discusses the works and the career of Charles Sanders Peirce as an experimental psychologist. Details of the psychological stage as it appeared about 1850; Description of Peirce's psychological writings and activities; Importance of the psychology of learning in Peirce's psychology.